Binding of a highly potent protease-activated receptor-2 (PAR2) activating peptide, [(3)H]2-furoyl-LIGRL-NH(2), to human PAR2 - Kanke, Toru (2005)
1. To determine the binding characteristics of a highly potent agonist for protease-activated receptor-2 (PAR2), 2-furoyl-Leu-Ile-Gly-Arg-Leu-amide (2-furoyl-LIGRL-NH(2)), whole-cell binding assays were performed utilising a radioactive ligand, [(3)H]2-furoyl-LIGRL-NH(2). 2. Specific binding of [(3)H]2-furoyl-LIGRL-NH(2) was observed in NCTC2544 cells, dependent upon PAR2 expression, and competitively displaced by the addition of unlabeled PAR2 agonists. Scatchard analysis of specific saturation binding suggested a single binding site, with K(d) of 122±26.1 nM and a corresponding B(max) of 180±6 f mol in 3.0 × 10(5) cells. 3. The relative binding affinities of a series of modified PAR2 agonist peptides obtained from competition studies paralleled their relative EC(50) values for Ca(2+) mobilisation assays, indicating improved binding affinities by substitution with 2-furoyl at the N-terminus serine. 4. Pretreatment of cells with trypsin reduced specific binding of [(3)H]2-furoyl-LIGRL-NH(2), demonstrating direct competition between the synthetic agonist peptide and the proteolytically revealed tethered ligand for the binding site of the receptor. 5. In HCT-15 cells endogenously expressing PAR2, the binding of [(3)H]2-furoyl-LIGRL-NH(2) was displaced by addition of unlabeled ligands, Ser-Leu-Ile-Gly-Lys-Val (SLIGKV-OH) or 2-furoyl-LIGRL-NH(2). The relative binding affinity of 2-furoyl-LIGRL-NH(2) to SLIGKV-OH was comparable to its relative EC(50) value for Ca(2+) mobilisation assays. 6. The binding assay was successfully performed in monolayers of PAR2 expressing NCTC2544 and human umbilical vein endothelial cells (HUVEC), in 96- and 24-well plate formats, respectively. 7. These studies indicate that [(3)H]2-furoyl-LIGRL-NH(2) binds to human PAR2 at its ligand-binding site. The use of this radioligand will be valuable for characterising chemicals that interact to PAR2.